Technological Growth and Hours in the Long Run: Theory and Evidence - Magnus Reif; Mewael F. Tesfaselassie; Maik H. Wolters (Economica, 2021)
Over the last few decades, hours worked per capita have declined substantially in many OECD economies. Using the standard neoclassical growth model with endogenous work–leisure choice, we assess the role of trend growth slowdown in accounting for the decline in hours worked. In the model, a permanent reduction in technological growth decreases steady-state hours worked by increasing the consumption–output ratio. Our empirical analysis exploits cross-country variation in the timing and size of the decline in technological growth to show that technological growth has a highly significant positive effect on hours. A decline in the long-run trend of technological growth by 1 percentage point is associated with a decline in trend hours worked in the range of 1–3%. This result is robust to controlling for taxes, which have been found in previous studies to be an important determinant of hours. Our empirical finding is quantitatively in line with the one implied by a calibrated version of the model, though evidence for the model's implication that the effect on hours works via changes in the consumption–output ratio is rather mixed.
Keywords: 330